Tinjauan Hukum Pemberian Upah Pada Buruh Dibawah Upah Minimum Provinsi - Aprilsesa, Tri Dian; Tahir, Muhammad; Aminah, Siti; Marnita, Marnita (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Getting a decent job and livelihood is a basic right of every citizen as a citizen that must be obtained. In its implementation, it cannot be denied that there are problems in employment, one of which concerns wages. However, in principle employers are prohibited from paying wages to workers/employees lower than the minimum wage. The purpose of analyzing the implementation of the provision of the minimum wage is expressly regulated in Article 23 paragraph (3) of Government Regulation Number 36 of 2021 concerning Wages as the Implementing Regulation of Law Number 11 of 2020 concerning Job Creation. If in the agreement, the wages paid are found to be lower or contrary to laws and regulations, the agreement may be null and void and the wage arrangements are carried out in accordance with the provisions of laws and regulations. The research method is normative juridical to analyze data by means of literature studies on secondary data which specifically discusses the norms contained regarding the Minimum Wage Provisions. Obstacles in the application of wages, both the UMP (Provincial Minimum Wage) and the UMK (Regency/City Minimum Wage), namely lower and middle-level companies that are unable to carry out the provisions of the UMP and UMK provisions themselves so that there is a gap between workers and companies. Even though the UMP is smaller than the UMK, there are small and medium-sized companies that are unable to provide good wages to workers according to the stipulations of the UMP. The welfare of workers in Indonesia has always increased from time to time because the magnitude of the increase in the minimum wage as a whole is lower than the increase in the price of the minimum necessities of life, so that workers cannot live a decent life.